1996
DOI: 10.1046/j.1365-2249.1996.d01-803.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung granulomatous response induced by infection with the intestinal nematode Nippostrongylus brasiliensis is suppressed in mast cell-deficient Ws/Ws rats

Abstract: SUMMARYCertain nematode infections induce eosinophil infiltration and granulomatous responses in the lungs. To examine the role of mast cells in the development of lung lesions, normal = and genetically mast cell-deficient Ws/Ws rats were infected with the nematode Nippostrongylus brasiliensis. In = rats, numbers of eosinophils in bronchoalveolar lavage fluid (BALF) increased significantly 3-7 days after infection, and granulomatous responses composed of histiocytes/macrophages and multinucleate giant cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…3). This result does not conflict with the fact that eosinophil infiltration into the lung is significantly decreased in Ws/Ws rats infected with N. brasiliensis [23], but suggests that there are two distinct pathways that lead to eosinophilia, i.e., a mast cell-dependent and a mast cell-independent pathway. The presence of two such pathways is supported by the finding that blockade of chymase by SUN-C8257 failed to abrogate blood eosinophilia completely (fig.…”
Section: Discussionmentioning
confidence: 73%
“…3). This result does not conflict with the fact that eosinophil infiltration into the lung is significantly decreased in Ws/Ws rats infected with N. brasiliensis [23], but suggests that there are two distinct pathways that lead to eosinophilia, i.e., a mast cell-dependent and a mast cell-independent pathway. The presence of two such pathways is supported by the finding that blockade of chymase by SUN-C8257 failed to abrogate blood eosinophilia completely (fig.…”
Section: Discussionmentioning
confidence: 73%
“…The average numbers of eosinophils as well as EPO levels at 24 and 48 h were slightly lower in WslWs than in +/+ rats, but this difference was not statistically significant. We previously reported that nematode-induced eosinophil infiltration in bronchoalveolar lavage fluid was significantly lower in WslWs than in +/+ rats (17). It was also reported that prior depletion of mast cells in the pleural cavity by local treatment with compound 48/80 significantly reduced antigen-induced eosinophil recruitment in sensitized animals (25).…”
Section: Discussionmentioning
confidence: 90%
“…These patients usually have elevated IgE antibody levels and symptoms consisting of dyspnea, often of an asthmatic type, suggesting that hypersensitivity mechanisms might be involved in the development of nematode-associated lung lesions (Phills et al, 1972). Like these human parasites, infection with the rodent intestinal nematode Nippostrongylus brasiliensis induces marked infiltration of eosinophils, an increase in the number of alveolar macrophages, development of granulomas, and an increase in the number of mast cells in the lungs In a previous study, we showed that genetically mast cell-deficient Ws/ Ws rats exhibited significantly lower levels of eosinophil infiltration and granuloma formation in the lungs than in normal + / + rats after N. brasiliensis infection, although elevated levels of IgE antibody did not differ between Ws/ Ws and + + rats, suggesting that mast cells play an important role for triggering the lung lesions (Arizono et al, 1996) . In the present study, we further investigated whether an antiallergic drug, ketotifen, would suppress the nematodeinduced lung lesions in rats.…”
Section: Introductionmentioning
confidence: 81%
“…Specific pathogen-free, male Brown Norway (BN/ Sea) rats were purchased from Seiwa Experimental Animals Co. (Fukuoka, Japan) . The animals, 8 weeks old (body weight 180-190 g) , received a subcutaneous injection of 2,000 infective-stage larvae of N. brasiliensis as described previously (Arizono et al, 1996) . A group of animals were sacrificed 28 days after infection.…”
Section: Animals and Nematode Infectionmentioning
confidence: 99%